Synthesis and Characterization of Ag/Ce1-xMnxO2-δ Oxidation Catalysts - Alami, David; Bulavin, Viktor (My University, 2013)
The aim of this work was to obtain samples of Ag-doped manganese-cerium mixed oxides and explore their characteristics. Six catalysts were prepared by the co-precipitation process followed by impregnation method for Ag incorporation. These catalysts were characterized in particular by means of Transmission Electron Microscopy (TEM), X-ray Diffraction (XRD), Temperature Programmed Reduction (TPR), BET surface area, and examined on the reaction of hydrogen peroxide catalytic decomposition. The samples obtained were solid solution nanoparticle agglomerates with irregular surface morphology. The results pointed out that the highest activity in oxidation reactions should possess Ag/Ce0.23Mn0.77O2-δ catalyst.
Keywords: catalytic activity; catalyst characterization; coprecipitation; mixed oxide; solid solution